Camel Brucellosis in Ethiopia: Seroprevalence and Associated Risk Factor - Wario Waji; Sultan Abda Neja (Journal of Veterinary Healthcare, 2023)
Camels are a significant source of income for nomadic populations in many developing countries, including Ethiopia. Camels are well adapted to dry and semi-dry regions, providing income, food security, and transportation. However, camel production and productivity are constrained by infectious diseases, such as brucellosis, which is a highly infectious bacterial disease that affects camels and humans worldwide. Brucellosis causes significant economic losses due to abortion, low herd fertility, and decreased milk production. In Ethiopia, the prevalence of camel brucellosis varies depending on factors related to the host, agent, climate, and management system, with a reported prevalence ranging from 0.5% to 11.9%. Accurate diagnosis of camel Brucellosis is essential for herd-based screening of animals. Although culturing the pathogen is the preferred method for diagnosis, serological tests such as Rose-Bengal plate test (RBPT), Enzyme-linked immunosorbent assay (ELISA), and Complement fixation test (CFT) and polymerase chain reaction (PCR) assays have been developed. Implementing effective diagnosis and surveillance systems to control the spread of brucellosis in animals and humans is very important, on top of awareness campaigns, vaccination programs, and suitable laboratory establishment recommended. Continued research is essential to maintain the health and productivity of camel populations, particularly in pastoral areas where camels play a significant role in the livelihood of communities. Therefore, the present paper views the seropositive prevalence and potential risk factors associated with camel brucellosis in Ethiopia.
Keywords: Brucellosis